Correlation of annealing temperature on physico-chemical properties and electrochromic performance of nebulizer spray-coated NiO films. Issue 2 (1st February 2023) - Ravi Dhas, C.; Santhoshi Monica, S. Esther; Venkatesh, R.; Sivakumar, R.; Nathanael, A. Joseph; Vignesh, R.; Arivukarasan, D.; Gnana Malar, K. C. Mercy; Keerthana, S.
Abstract: Nickel Oxide (NiO) thin films were deposited over glass and FTO substrates using nebulizer spray pyrolysis technique. The influence of various annealing temperatures (400, 450, 500 and 550 °C) on film stoichiometry and its subsequent effect on physical and electrochromic properties were studied. Structural information, chemical state and change in morphological properties of the deposited films concerning the film stoichiometry and concentration of cationic vacancy (VNi ) induced Ni 3+ ions are discussed with the help of XRD, XPS, HR-SEM, EDS and AFM. The variation of optical parameters associated with the presence of defects in NiO is reported from UV-Vis spectroscopic analysis. Electrochromic performance of the prepared films was evaluated using cyclic-voltammetry, chronoamperometry, chronocoulometry and iono-optical electrochemical measurements. Enhanced electrochromic behavior with a rapid switching response time of 0.3/0.5 s of bleached/colored states respectively was realized for NiO film with relatively higher concentration of Ni 3+ . Graphical Abstract: UF0001